أثر الاستثمار الأجنبي المباشر على النمو الاقتصادي في تركيا خلال الفترة (2006 ــ 2016 - سلامي, أحمد; ساحل, محمد; بن تفات, عبد الحق (University of Eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى الكشف عن واقع العلاقة بين الاستثمار الأجنبي المباشر والنمو الاقتصادي في تركيا للفترة (2006ـ2016)، وتحقيقا لهذه الغاية تم اجراء معالجة قياسية للبيانات باستخدام اختبار التكامل المشترك، واستنادا إلى النتائج المتوصل إليها فإنه لا توجد علاقة توازنية بين الاستثمار الأجنبي المباشر والنمو الاقتصادي في تركيا خلال الفترة التي تم تحليلها، وهذه النتيجة تدعم وتتوافق مع نتائج العديد من الدراسات التي تناولت حالة الاقتصاد التركي، ولعل أبرزها : دراسة (2015) Mustafa Gerceker ؛ دراسة (2014) et al Mustafa Tahir Demirsel ودراسة (2014) Ahmed Abdul Rahman Khder Aga، ويمكن تفسير ذلك بطبيعة الاستثمار الأجنبي المباشر الوافد إلى تركيا والذي اتسم بالتذبذب، علاوة على أنه يتم بشكل أساسي من خلال عمليات الاندماج والاستحواذ، بحيث لا يخلق التأثير المتوقع على الناتج المحلي الاجمالي. ناهيك عن الأداء غير المستقر للنمو بسبب التطورات الدولية والاقليمية التي أثرت سلبا على تركيا. في هذا السياق، أوصت الدراسة بضرورة اعتماد سياسات لجذب الاستثمارات التي تعتمد على إنشاء مشروعات جديدة في تركيا بغية تعزيز نموها الاقتصادي. Abstract: This study aims to revealing the reality of the relationship between foreign direct investment and economic growth in Turkey for the period 2006-2016. To this end, econometric data processing was carried out using the co-integration test. Based on the results reached, there is no balance relationship between FDI and economic growth In Turkey during the period analyzed, and this result supports and corresponds to the results of several studies on the state of the Turkish economy, notably: Mustafa Gerceker study (2015); Mustafa Tahir Demirsel et al study (2014) and Ahmed Abdul Rahman Khder Aga study (2014). Can be explained by nature FDI inflows to Turkey, characterized by volatility, and mainly through mergers and acquisitions, so as not to create the expected impact on GDP. Not to mention the unstable performance of growth due to international and regional developments those have negatively affected Turkey. In this context, the study recommended the adoption of policies to attract investments that depend on the establishment of new projects in Turkey in order to promote economic growth
The Impact of Foreign Direct Investment on Economic Growth in Turkey During the period (2006-2016)
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: استثمار أجنبي مباشر ؛ نمو اقتصادي ؛ تركيا ؛ تكامل مشترك.; FDI; Economic Growth; Turkey; co-integration. Jel Classification Codes: F21; F43